A systematic process for creating and appraising clinical vignettes to illustrate interprofessional shared decision making. Issue 5 (September 2014) - Stacey, Dawn; Brière, Nathalie; Robitaille, Hubert; Fraser, Kimberly; Desroches, Sophie; Légaré, France
Abstract Vignettes and written case simulations have been widely used by educators and health services researchers to illustrate plausible situations and measure processes in a wide range of practice settings. We devised a systematic process to create and appraise theory-based vignettes for illustrating an interprofessional approach to shared decision making (IP-SDM) for health professionals. A vignette was developed in six stages: (1) determine IP-SDM content elements; (2) choose true-to-life clinical scenario; (3) draft script; (4) appraise IP-SDM concepts illustrated using two evaluation instruments and an interprofessional concept grid; (5) peer review script for content validity; and (6) retrospective pre-/post-test evaluation of video vignette by health professionals. The vignette contained six scenes demonstrating the asynchronous involvement of five health professionals with an elderly woman and her daughter facing a decision about location of care. The script scored highly on both evaluation scales. Twenty-nine health professionals working in home care watched the vignette during IP-SDM workshops in English or French and rated it as excellent (n = 6), good (n = 20), fair (n = 0) or weak (n = 3). Participants reported higher knowledge of IP-SDM after the workshops compared to before (p < 0.0001). Our video vignette development process resulted in a product that was true-to-life and as part of a multifaceted workshop it appears to improve knowledge among health professionals. This could be used to create and appraise vignettes targeting IP-SDM in other contexts.